PENDIDIKAN ALTERNATIF BERBASIS KOMUNITAS: STUDI PADA SEKOLAH QARYAH THAYYIBAH - Satya Manggala Pragolapati; Wiwik Widayati; Supratiwi . (Journal of Politic and Government Studies, 2013)
Abstract The phenomenon of community governance or people who are able to plan and make decision that affect directly to the community itself such as in educational service keeps popping up. Created an alternative school as in Qaryah Thayyibah Alternative School was one of example of it. This study aims to determine the role of Qaryah Thayyibah in providing education services through an alternative school model and see the level of public acceptance of the school. This study used a qualitative approach which describes research in the form of a description without using numbers and classified as non-experimental descriptive type because researcher is just trying to describe and explain from what is obtained from the field without performing experiments on the respondents. The study was conducted over three months from the date of 21 December 2012 - 22 December 2012 through observation, interviews and documentation of the managers, assistants, community, government and other literature relating to the Qaryah Thayyibah Alternative School. The results of this study describes role of Qaryah tayyibah in providing education services through its alternative school models of learning and school management. Although the school management is still low but has sought involve the community and parents in the learning process and school management. The results also explain the level of public acceptance is still relatively low in the existence Qaryah tayyibah Alternative School. Suggestions given for Qaryah Thayyibah Alternative School are the need for strengthening the functions of the school management and the need for two-way communication between the school and the community who both involved and not involved in the educational process.